2014
DOI: 10.3389/fncel.2014.00308
|View full text |Cite
|
Sign up to set email alerts
|

8-Methoxypsoralen is a competitive inhibitor of glutathione S-transferase P1-1

Abstract: The blood-brain barrier (BBB) is known to protect healthy brain cells from potentially dangerous chemical agents, but there are many evidences supporting the idea that this protective action is extended to tumor cells. Since the process of angiogenesis in brain tumors leads to BBB breakdown, biochemical characteristics of the BBB seem to be more relevant than physical barriers to protect tumor cells from chemotherapy. In fact, a number of resistance related factors were already demonstrated to be component of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Furthermore, high GSH pool levels or elevated expression of GSTP1, GSTZ1, or other glutathione pathway genes could serve as biomarkers for the stratification patients. In this study, we used BSO, an inhibitor of GCL, to deplete the GSH pool, but specific inhibitors of GSTP1 such as 8-methoxypsoralen are currently under development (51). The use of agents to deplete the GSH pool in combination with conventional therapeutics or molecularly targeted drugs thus warrants further study in high-risk neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high GSH pool levels or elevated expression of GSTP1, GSTZ1, or other glutathione pathway genes could serve as biomarkers for the stratification patients. In this study, we used BSO, an inhibitor of GCL, to deplete the GSH pool, but specific inhibitors of GSTP1 such as 8-methoxypsoralen are currently under development (51). The use of agents to deplete the GSH pool in combination with conventional therapeutics or molecularly targeted drugs thus warrants further study in high-risk neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a 72-h incubation with 0.4 mM 8-MOP promoted death on 41.68% of human glioblastoma GL-15 cells. Indeed, in our study 0.2 mM 8-MOP was more effective against GL-15 cells, which are extremely resistant to TMZ (de Oliveira et al, 2014), than 0.2 mM TMZ against GOS-3 and U-87 MG glioma cells (Patel et al, 2008).…”
Section: Discussionmentioning
confidence: 43%
“…This effect is probably due to the antiproliferative action of 8-MOP, since the reduction of cell density in the culture is itself a stimulus for vimentin expression, which also occurs after treatment with traditional chemotherapy (Trog et al, 2008). We have recently demonstrated that 8-MOP also inhibits the glutathione S-transferase p (GSTP1) activity and increases cell susceptibility to apoptosis (de Oliveira et al, 2014), which could explain the proapoptotic action of 8-MOP at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Many GSH analogs, small-molecules and natural products have been generated as GSTP1 inhibitors. 2 Reversible GSTP1 inhibitors include 8-methoxypsoralen, piperlongumine, aloe emodin, and benstatin A, 2, 6, 7 as well as Telintra (Ezatiostat), which is currently in clinical trials for the treatment of myelodysplastic syndrome. 8, 9 GSTP1 contains four cysteine residues, two of which (C47 and C101) have been shown to be highly reactive and targeted by irreversible GSTP1 inhibitors.…”
mentioning
confidence: 99%